Estudo fitoquímico e investigação das atividades antioxidante, antimicrobiana e larvicida das cascas de Annona salzmannii A. DC. (Annonaceae) - Cruz, Pedro Ernesto Oliveira da (2011)
The presente work describes the results obtained from the phytochemical studies bioguided of crude extracts of the bark of A. salzmannii, a species belonging to the Annonaceae family, front to tests of antioxidant, antimicrobial, and insecticide activities against larvae of the mosquito Aedes aegypti. From the hexane extract were isolated five compounds, been three sesquiterpenes (caryophyllene oxide, spathulenol, and selin-11-en-4a-ol); and two steroids (stigmast-4-en-3-one and - sitosterol). From the chloroform alkaloidal fraction of the methanolic extract were isolated seven alkaloids: liriodenine, 10-methoxyliriodenine, anonaine, asimilobine, reticuline, cleistopholine, and a mixture of alkaloids anonaine and xylopine. The assay of antioxidant activity revealed that the methanol extract (3583.02 μmol of TE g-1) and its fractions, chloroform alkaloidal fraction (5291.77 μmol of TE g-1) and chloroform neutral fraction (2047.54 μmol of TE g-1) showed significant antioxidant activity, mainly the chloroform alkaloidal fraction. Among the alkaloids isolated and tested, asimilobine was the most active of them with antioxidant activity of 2.09 TE relative. For antimicrobial assay, the best results were observed for methanol extract and chloroform alkaloidal fraction against Staphylococcus aureus (ATCC14458), Escherichia coli (ATCC 10799), Candida tropicalis (ATCC 157), and C. dubliniensis (ATCC 777). Among the alkaloids isolated and tested, all showed significant results with MIC values between 25-100 mg.mL-1, mainly the alkaloids anonaine, asimilobine, and liriodenine against Staphylococcus aureus penicilinase- (8-), S. epidermidis (ATCC 12228), S. epidermidis (6ep), and Candida dubliniensis (ATCC 778157). To the test of larvicidal activity, only the hexane extract and the fractions of methanol extract showed activity below 700 mg.mL-1. The caryophyllene oxide showed activity of 167 mg.mL-1. The results obtained confirm that A. salzmannii is a typical species of the Annonaceae family, and a promising source of biologically active compounds.